The Effect of the Scramble-Type Cooperative Learning Model Assisted by Picture Cards on Students' Reading Ability - Indriliani, Riska Wahyu; Cahyaningtyas, Andarini Permata (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
The purpose of this study was to investigate the effectiveness of the Scramble-type cooperative learning model, assisted by picture cards, on the reading ability of second-grade students at SD Negeri Kalibanteng Kidul 01. This research employed an experimental method using a Nonequivalent Control Group Design. The study population consisted of 60 students from two classes: Class II B (control group) and Class II C (experimental group), each comprising 30 students. The sample was selected using purposive sampling. Data were collected through oral reading tests. Data analysis involved the use of the Paired Sample t-test to measure the within-group effect, and the Independent Sample t-test to compare outcomes between groups. A significance level of 0.05 (two-tailed) was applied in both tests. The findings indicate that the Scramble-type cooperative learning model assisted by picture cards significantly improved students' reading ability. The Paired t-test results for the experimental class yielded a significance value of 0.000, which is less than 0.05, confirming the effectiveness of the intervention. Similarly, the Independent t-test showed a significance value of 0.013 (p < 0.05), indicating a statistically significant difference in reading performance between the experimental and control groups. These results demonstrate that the use of the Scramble cooperative learning model, when supported by picture cards, is more effective in enhancing students’ reading skills compared to conventional learning methods. Abstrak: Tujuan penelitian ini adalah untuk mengetahui kemampuan membaca peserta didik menggunakan model pembelajaran kooperatif tipe scramble berbantu kartu gambar yang diberikan pada kelas eksperimen SD Negeri Kalibanteng Kidul 01. Penelitian ini merupakan penelitian eksperimen, dengan desain Nonequivalent Control Group Design. Populasi penelitian ini sebanyak 60 peserta didik dari dua kelas B dan C yang terdiri dari II B (kontrol) 30 peserta didik dan kelas II C (eksperimen) 30 peserta didik. Penentuan sampel di dalam penelitian ini menggunakan purposive sampling. pengumpulan data menggunakan tes lisan. dalam menganalisis data menggunakan uji T yaitu uji paired t-test dengan taraf sig. (2-tailed) < 0,05 dikatakan maka ada pengaruh. Hasil penelitian yang telah dilakukan di SD Negeri Kalibanteng Kidul 01 menunjukan bahwa model pembelajaran kooperatif tipe scramble berbantu kartu gambar memberikan pengaruh yang signifikan dalam kemampuan membaca peserta didik, Dibuktikan bahwa nilai 0,000 < 0,05 model pembelajaran yang diterapkan di kelas eksperimen berpengaruh terhadap kemampuan membaca peserta didik. Serta pada Uji Independent T-test, dengan taraf nilai sig. (2-tailed) > 0,05 dikatakan maka ada perbedaan. Model pembelajaran kooperatif tipe scramble berbantu kartu gambar berpengaruh secara signifikan dibanding pembelajaran konvensional terhadap kemampuan membaca peserta didik, dapat dibuktikan bahwa hasil uji independent t-test, nilai sig. (2-tailed) yang memperoleh 0.013 karena 0,013 < 0,05 maka dapat disimpulkan model pembelajaran kooperatif tipe scramble berbantu kartu gambar memberikan peningkatan terhadap kemampuan membaca dibanding model pembelajaran konvensional.